Adenomas involving the extrahepatic biliary tree are rare but have an aggressive clinical course - Loh, Kah Poh; Nautsch, Deborah; Mueller, James; Desilets, David; Mehendiratta, Vaibhav (Endoscopy International Open, 2016)
Biliary adenomas that are usually found in surgically removed gallbladders are rare, but can also occur in the extrahepatic biliary tree. We present a case series of extrahepatic bile duct adenomas at our institution, along with a review of the literature. All three patients with extrahepatic biliary adenomas (two in the common bile ducts, one in the hepatic duct) were female with a mean age of 74 years. On initial presentation, none of the patients had obstructive jaundice but two of the three patients had symptoms of biliary origin. Case 1 is an 85-year-old woman with an incidental biliary dilation seen on chest imaging; endoscopic ultrasound revealed a sessile adenomatous polyp in the distal bile duct. The patient refused surgery and presented with occlusive biliary stricture and jaundice 5 months after initial presentation, with cytology confirming malignant progression. Case 2 is a 78-year-old woman with a history of primary sclerosing cholangitis and who presented with cholangitis, and Gram-negative sepsis. A polypoid lesion was seen on imaging in the common hepatic duct and direct cholangioscopy with biopsies confirmed the presence of adenoma with high grade dysplasia. The patient underwent successful total bile duct resection and hepaticojejunostomy but represented 1 year later with diffuse metastatic disease to the bone, liver, and peritoneum. Case 3 is a 61-year-old woman who presented with symptoms suggestive of gallbladder pathology and was found to have a polypoid bile duct lesion on intraoperative cholangiogram. Endoscopic retrograde cholangioscopy showed an adenomatous polyp with high grade dysplasia involving the distal common bile duct. The patient underwent distal bile duct resection with choledochojejunostomy but presented with jaundice 4 years after surgery. She was found to have adenocarcinoma involving the small bowel in the Roux limb of jejunum and transverse colon. All three patients in our series presented with interval gastrointestinal malignancy and we therefore recommend aggressive surgical intervention and close postoperative surveillance when diagnosis of extrahepatic bile duct adenoma is made.